Daya Hidup Spermatozoa Babi Large White Dengan Penambahan Ekstrak Cairan Vesikula Seminalis Sapi Bali (VITALITY OF SPERMATOZOA IN WHITE LARGE BREED SWINES ADDED BY EXTRACTED LIQUID OF BALI CATTLE SEMINAL VESICLE) - Aini, Khaza; Pemayun, Tjok Gde Oka (Buletin Veteriner Udayana, 2015)
The purposes of this study was to know the vitality of spermatozoa from large white breedswines in diluents phosphat egg yolk added by extracted liquid of bali cattle seminal vesicle storedin a temperature of four to five degree celcius. this study used completely randomized design with 4 treated group, each group repeated five times. first group were semen dilueted with phosphat eggyolk without added by extracted liquid of seminal vesicle as control; second group were semendilueted with phosphat egg yolk added by zero point five percent concentration of extracted liquidof seminal vesicle; third group were semen diluted with phosphat egg yolk added by one percentconcentration of extracted liquid of seminal vesicle, and fourth group were semen dilueted withphosphat egg yolk added by one point five percent concentration of extracted liquid of seminalvesicle. the observation was conducted to know the percentage of alive spermatozoa every 12 hour.the results of this study showed that the addition of extracted liquid of seminal vesicle wassignificant effected the vitality of spermatozoa in which the best concentration of extracted liqud od seminal vesicle was one percent.
Keywords: spermatozoa; swines; seminal vesicle; vitality